Fabrication of CNTs supported binary nanocomposite with multiple strategies to boost electrochemical activities. (1st July 2021) - Aadil, Muhammad; Zulfiqar, Sonia; Shahid, Muhammad; Agboola, Philips O; Al-Khalli, Najeeb Faud; Warsi, Muhammad Farooq; Shakir, Imran
Highlights: CoS2 /CNTs nanocomposite was fabricated via hydrothermal and post-annealing approach. The freestanding design and 3D nickel foam were used to improve the kinetics of the electrochemical reaction. The CoS2 /CNTs@NF electrode showed higher specific capacity (499.8 C g −1 ) than that of pristine CoS2 @NF electrode (387.6 C g −1 ) at 1 A g −1 . The nanocomposite also exhibit superior rate capability and cyclic-stability than the pristine CoS2 sample. Abstract: Electroactive materials with higher surface area, porous structure, higher conductivity, and self-supported design are considered promising candidates for electrochemical applications. The fabrication of an electrode material with a unique design having all the features mentioned above is a major challenge for electrochemical researchers. In this work, pristine CoS2 nanoparticles and CoS2 /CNTs nanocomposite have been prepared and decorated directly on nickel foam (NF) using a two-step approach: hydrothermal and post-annealing, for energy storage applications. The CoS2 /CNTs@NF electrode shows superior performance as it has a specific capacity (Csp ) of 499.8 C g −1 @ 1 A g −1 and excellent cyclic stability of 90.8% after 6000 GCD cycles @ 12 A g −1 . The CNTs-supported CoS2 sample displays a minimum capacitance loss of 13.5% by increasing the applied current density from 1 to 12 A g −1, demonstrating its excellent rate-capability. Furthermore, the EIS results show that the value of the charge transfer resistance (RCT ) and the mass transfer resistance for CoS2 decreases after its nanocomposite formation with conductive CNTs. The exceptional electrochemical activity of the CoS2 /CNTs@NF electrode has been attributed to the synergistic effect of its self-standing design, larger specific surface area, porous-nanostructure, and hybrid composition. The present study provides a new way of designing the electrode material with integrated electrochemical features. Graphical abstract: Image, graphical abstract